2018
DOI: 10.1136/bjophthalmol-2017-311349
|View full text |Cite
|
Sign up to set email alerts
|

Deep anterior lamellar keratoplasty: dissection plane with viscoelastic and air can be different

Abstract: BB obtained by injection of viscoelastic and air can be different. The former tends to occur at the site of injection, especially with midstromal injections, takes the form of tissue separation by stretch and tearing and does not cleave in a consistent plane like air. Surgeons should be aware of IBB created by viscodissection and not confuse it for a type1 BB. Intraoperative OCT should help identify IBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, it has been recently shown that unlike with air injection, the plane of insertion of the needle tip is crucial, because with mid stroma injections of viscoelastic, an intrastromal bubble, mimicking a Type-1 BB, often occurs. [ 53 ]…”
Section: Deep Anterior Lamellar Keratoplastymentioning
confidence: 99%
“…However, it has been recently shown that unlike with air injection, the plane of insertion of the needle tip is crucial, because with mid stroma injections of viscoelastic, an intrastromal bubble, mimicking a Type-1 BB, often occurs. [ 53 ]…”
Section: Deep Anterior Lamellar Keratoplastymentioning
confidence: 99%
“…Recipient beds were trephinated using 3.0-6.0 mm skin biopsy punches (Stiefel Laboratories, Inc., Middlesex, United Kingdom) or using 7.0-8.0 mm diameter vacuum trephine and vacuum donor punch (Moria, Antony, France) along the size and location of underlying lesions. For DALK, the big bubble technique or viscodissection was used for recipient bed preparation 17 . For elongated lesions that could not be grafted with commercially available punches or trephine, such as Terrien marginal degeneration or marginal keratitis, recipient lesions were manually resected using a no.…”
mentioning
confidence: 99%